Above the waterfall [large type] : a novel - Rash, Ron, 1953- (HarperLuxe, an imprint of HarperCollinsPublishers, 2015)
When an elderly resident is accused of poisoning a North Carolina mountain resort's trout stream, Les, the nearby town's longtime sheriff, and Becky, a park ranger and newcomer, work together to solve the crime.